Lockdown Impact on Stress, Coping Strategies, and Substance Use in Teenagers - Bourduge, Cédrine; Teissedre, Frédérique; Morel, Florence; Flaudias, Valentin; Izaute, Marie; Brousse, Georges (Frontiers in Psychiatry, 2022)
Background: In response to the COVID-19 pandemic, the French government took many measures, the most notable of which was a national lockdown on 17 March 2020. Its effects have been widely studied, but to our knowledge, no study has sought to determine how adolescents have adapted to cope with this situation. The present study set out to explore teenagers' stress levels, coping strategies, and substance use during this period. Method: This cross-sectional study rides on an existing prevention program interviewed 348 French middle school students (209 girls and 139 boys) in grade 8 (Mage = 13.45; SDage = 0.54) using an online questionnaire between March 17 and May 11, 2020.The study examined the teenagers’ perceived stress, coping strategies they had used, including recent use of tobacco, alcohol and cannabis, during COVID-19 lockdown. Results: Teenagers reported lower perceived stress during lockdown than usually, with a significant decrease for girls. Those who perceived the least social support reported the highest levels of stress. The strategies of planning, behavioral disengagement, self-distraction, positive reframing, acceptance, and religion were used more than usual, while active coping and self-blame were used less. Acceptance was the most often used strategy and a source of decreased stress during lockdown.A significant decrease in recent tobacco, alcohol and cannabis use was also observed. Conclusion: Changes in the use of coping strategies, withdrawal from the stressful school environment, and greater exposure to parents than to peers caused adolescents to be less stressed and to decrease their substance use during the lockdown.